Dropout tendency in higher education : a qualitative study of International students in Malaysia - Mohd Azrin Mohd Nasir; Nor A’tikah Ali; Suzila Ismail; Ros Idayuwati Alaudin; Farah Nadia Mohd Faudzi (Penerbit Universiti Kebangsaan Malaysia, 2022)
Dropout is an unending issue and a worldwide concern. Therefore, this study aims to investigate the potential factors of dropout tendencies for international students in one public university in Malaysia. Twelve international undergraduate students from different majors were interviewed to understand their learning experiences, adaptation process and intentionality to dropout. The data were collected primarily through a focus group and a structured interview, then analysed using NVivo. The findings revealed six themes: (i)financial difficulties, (ii) lack of cultural understanding, (iii) language ability, (iv) self-adjustment, (v)university engagement, (vi) accommodation, and services. These themes were predominantly associated with three specific areas of Tinto’s Theory: academic problem, failure to integrate socially, and commitment to students and universities. Knowing about the causes of the students leaving the institution may help the university move from theory into action. The information will assist the university and college to look into institutional practices to enhance engagement, develop effective policies and programmes, and then invest in a better facility and staff development to increase student retention at the higher education.